New Method for OC Relay Coordination - Ameer Aqeel Kamoona; Ahmed Najm alfadli; Israa Ali Alshabeeb (Journal of Electrical and Computer Engineering)
Protection relays design and manufacture have arrived to a new level of advancement; hence, numerical relays have appeared recently. They combine all the functions of monitoring, control, and protection in one device. Also these relays have the ability to communicate with each other to share statuses and orders using GOOSE (generic object‐oriented substation events) messages based on communication protocols such as IEC61850. In this paper, a proposed method for overcurrent (OC) relay coordination has been introduced based on numerical relay features of several setting groups and communication capability. This work supposes that the coordination between feeder, bus section, and incomer protection relays, in a substation of single busbar configuration with bus sectionalizer (i.e., bus section), depends on the status of the bus section circuit breaker (CB) as a criterion for determining active relay setting group, to achieve a faster tripping action. ETAP has been used as a simulation software environment. And the simulation results show the advantages of the proposed method in reducing the time needed by the relay to clear the electrical fault. Siemens SIPROTEC series have been used as an example of numerical relays, specifically 7SJ64 as OC relay, which exists in the ETAP library.